Roles of Secreted Phospholipases A2 in the Mammalian Immune System - Krizaj, Igor (Protein and Peptide Letters, 2014)
Secreted phospholipase A2 (sPLA2) molecules constitute a family of proteins that are involved functionally in many biological processes. In particular, they participate in diverse pathophysiological settings as enzymes that release free fatty acids and lysophospholipids from phospholipids in biological membranes, or as ligands for various cellular receptors. In this review the confirmed or expected functions of sPLA2s in the mammalian immune system are surveyed. Some of the twelve mammalian sPLA2 molecules constitute part of the so-called innate immune system by virtue of their antibacterial, antiviral and antifungal activities. They are also involved in acute inflammation, a protective reaction of the body to infection or injury. The acute inflammation sometimes escapes regulation, becomes chronic and can evolve into a severe pathology. One or more types of sPLA2 are involved in asthma, rheumatoid arthritis, sepsis, atherosclerosis, myocardial infarction, Crohn’s disease, ulcerative colitis and cancer. sPLA2s are thus important therapeutic targets as well as biotherapeutic molecules. Improving the selectivity of inhibitors of sPLA2s to be able to target a particular sPLA2 could therefore be one of the most important tasks for future research.
Keywords: bacterial defence